As miniaturas na imaginária missioneira : o acervo do Museu Monsenhor Estanislau Wolski - Ahlert, Jacqueline (2008)
In this study are analyzed the remnants miniatures of the material culture of the jesuitical-guarani missions in exposition in the Museum Monsenhor Estanislau Wolski, located in the city of Santo Antônio das Missões, Rio Grande do Sul, Brazil. These saints images, of the Virgin and of the Christ, produced by guarani indians and jesuitical missionaries between the XVII and XVIII centuries in the Jesuitical Province of Paraguay, aren t understood only as objects produced in past times, but in the different representations between the material and the imaginary built by the levels of relationship partner-cultural that were presents: Spanish colonial authority, Catholic church, guarani indians and missionaries, and that assigned for the materialization of a missioneiro style of art, with characteristics native to a mixed race root, where the intervention of the guarani introduced the christian icons in the historicity that defined the formation of a style built from new meanings and interpretations strongly appointed by the guarani mental (animism) ancestral culture. These representations are studied by the light of the context of a process of negotiations resulting of the contact intercultural between europeans and amerindians and, in this sense, about the beacons of geographical and cultural borders. The persuasive force of the baroque, educational that permeated the atmosphere reducional, and the logic counter-reformation of enlargement of the catholic domains also are considered in the perspective of the incorporation of the christian rules. The miniatures show up the transposition of the sacred environment of the church for the individual space of the domestic worship. In the space of the subjectivity the native aesthetics fooled to emerge, resymbolizing the catholic iconography.